Transferring the Moral Rights of Translation to the Heirs between International Conventions and Arab Laws "A Comparative Study" - Alhendi, Noor; Baniamer, Asem (Dirasat: Human and Social Sciences, 2022)
This study clarifies the issue of transferring the moral rights of translation to the heirs in the international conventions for the protection of literary and artistic property and Arab laws countries for the protection of copyright and neighboring rights in a comparative, balanced way, and this came through the inventory and statement of the moral translation rights mentioned in international conventions and the laws of Arab countries, And to determine the mechanism of their transfer to the heirs, and to put forward recommendations that contribute to repairing the gap in what international conventions and Arab laws have limited in regulating the issue of the transfer of this type of rights to the heirs after the death of the translator.